Calidad de atención y satisfacción del usuario externo en consulta Privada de ginecología, Huamachuco - De la Cruz Asto, Reduvina Margarita (2022)
The objective of the research work is to determine the relationship between the quality of care and the user's satisfaction in a private Gynecology practice. The sample consisted of 86 women who attended a private gynecology clinic who met the inclusion criteria and wished to participate voluntarily. Two instruments were applied to measure the quality and satisfaction of the user and determine the relationship of the variables under study. These instruments have a validity of 0.957 and 0.932, respectively, which indicates that both instruments are valid. A Cronbach's Alpha reliability index of α = 0.929 and 0.741 was obtained, which indicates that both instruments are reliable. For data processing, computer tools such as Excel and SPSS V21 statistical software were used. In relation to the results, we found that the satisfaction of the external user was 96.5%, little satisfied 3.5%; the level of quality 86% had a high level and 14% had a medium level of quality of care. In addition, of the 100% of users who rate the care at a medium level, 83.3% are satisfied and of the 100% of users who rate the care at a high level, 98.6% are satisfied with the service provided and only 1.4% qualify as unsatisfied, concluding that with a significance level of 5% there is no relationship between variables, rejecting the hypothesis proposed by this research.